Deworming school children in Ethiopia: The importance of a comprehensive approach - Jemal Ali1; 7; Allison Polland2; David Adlerstein3; Yirga G Gziabher4; Galia Sabar5; Yonat Liss6; Zvi Bentwich1; 6 (Open Journal of Tropical Medicine - Peertechz Publications, 2019)
Introduction: A quarter of the world's population, most commonly in developing countries like Ethiopia, are infected with intestinal parasites. School age children are the most affected segment of the population. The World Health Organization (WHO) recommends periodic deworming of all at-risk people living in endemic areas. Methods: In 2009, Ben Gurion University, in partnership with the NALA Foundation and in collaboration with the Organization for Social Services and AIDS (OSSA), an Ethiopian non-governmental organization, and the health and education bureau of Tigray Regional State, launched a deworming project for school children in Mekele City, Ethiopia. During its four years of implementation (2009-2012), we evaluated the effi cacy of this intervention in controlling helminthic infection in participating schools. The program entailed a comprehensive approach, combining intensive health education with water sanitation and mass drug administration and with pre- and post-intervention stool surveys, during each year of the intervention.